2001
DOI: 10.1093/oxfordjournals.schbul.a006850
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Poor Outcome Patients With Lifelong Schizophrenia

Abstract: Gender effects have been reported quite consistently in schizophrenia, with male patients having an earlier age of onset, poorer functional outcome, greater negative symptoms and cognitive impairment, and less severe positive symptoms. Because age of onset, cognitive impairments, and negative symptoms are all correlated with poorer functional status, it is not clear if previously reported gender differences in symptoms are just recapturing gender differences in functional outcome. In this study, 205 geriatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
2
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 57 publications
(68 reference statements)
7
55
2
6
Order By: Relevance
“…However, both the current and other previous studies have found that males have worse negative symptoms, response to antipsychotics, and cognitive deficits than females with schizophrenia [6][7][8][9][11][12][13]. This may affect more daily life and self-medical protection awareness for male individuals and lead to their poorer glycemic control.…”
Section: Accepted M Manuscriptmentioning
confidence: 79%
See 1 more Smart Citation
“…However, both the current and other previous studies have found that males have worse negative symptoms, response to antipsychotics, and cognitive deficits than females with schizophrenia [6][7][8][9][11][12][13]. This may affect more daily life and self-medical protection awareness for male individuals and lead to their poorer glycemic control.…”
Section: Accepted M Manuscriptmentioning
confidence: 79%
“…Male individuals have an early age of onset, worse negative symptoms, and a worse response to antipsychotics than female individuals with schizophrenia [6][7][8][9]. A recent study found a lower prevalence of diabetes in male than female individuals with schizophrenia [10].…”
Section: Introductionmentioning
confidence: 99%
“…Na regressão logística, o procedimento consistiu em selecionar inicialmente as variáveis que na análise univariada apresentaram valor p ≤ 0, 25, exceção feita para idade e duração da doença, que entraram no modelo independentemente do valor-p apresentado devido à sua relevância clínica 1,11,20,21,22 . A premissa de chances proporcionais foi testada para todas as variá-veis individualmente e para o modelo final 19,23 .…”
Section: Análise De Dadosunclassified
“…Diferenças foram detectadas quanto à sua distribuição, características, evolução 10 e, mais recentemente, na qualidade de vida 4,6,7,8,9,11,12 . A maioria desses estudos indica que homens e mulheres possuem diferentes experiências com a esquizofrenia, mas pouco se conhece sobre o reflexo dessas diferenças na percepção do paciente sobre sua qualidade de vida e, principalmente, sobre as suas implicações para a prática clínica e para o planejamento dos serviços de saúde mental 10 .…”
Section: Introductionunclassified
“…A doença surge geralmente em adultos jovens, com maior prevalência (Saha, Welham, Chant, & McGrath, 2006) e início mais precoce (Moriarty et al, 2001), no sexo masculino. Os doentes apresentam uma baixa taxa de matrimónio e altas taxas de divórcio e desemprego de longa duração, o que frequentemente leva à pobreza e à situação de sem-abrigo (Thornicroft et al, 2004); os que têm perturbações psicóticas graves apresentam, mais frequentemente, comportamento agressivo (Hodgins & Muller-Isberner, 2004).…”
Section: Esquizofreniaunclassified